Are general practitioners well informed about fibromyalgia?. (22nd July 2015) - Kianmehr, Nahid; Haghighi, Anousheh; Bidari, Ali; Sharafian Ardekani, Yaser; Karimi, Mohammad Ali
Abstract: Aim: Fibromyalgia syndrome (FMS) is a common rheumatologic disorder characterized by easy fatigability, widespread musculoskeletal pain and sleep disorder. In spite of its high prevalence, general practitioners, as primary care providers, seem to have inadequate knowledge about FMS. This study aimed to assess Iranian general practitioners' knowledge about FMS and its treatment. Method: A detailed questionnaire (including items on signs and symptoms, diagnostic criteria and treatment) was completed by 190 general practitioners (54.7% male; mean age: 41 years). Data analysis was performed with SPSS for Windows 15.0 and awareness about all aspects of FMS was reported as percentages. Results: About one‐third (30%) of the participants had seen at least one case of FMS during their practice. Most subjects (62.7%) claimed to know 1–6 tender points. Only 3.2% knew 16–18 points. The common proposed symptoms of FMS were widespread pain (72.6%), excessive fatigue (72.6%), weakness (60.5%), sleep disorder (36.3%), anxiety (34.7%) and depression (34.2%). Wrong symptoms including elevated erythrocyte sedimentation rate and C‐reactive protein, arthritis, joint swelling, weight loss and abnormal radiologic findings were selected by 27.9%, 18.9%, 14.7%, 12.6% and 2.1% of the physicians, respectively. Moreover, selective serotonin reuptake inhibitors, tricyclic antidepressant and pregabalin were identified as treatment options for FMS by, respectively, 45.8%, 22.1% and 15.3% of the participants. Finally, 52.1% and 23.7% of the subjects incorrectly considered nonsteroidal anti‐inflammatory drugs and corticosteroids as treatment modalities for FMS. Conclusion: Iranian general practitioners are not well informed about FMS. Therefore, FMS should be specifically integrated in continuing medical education programs and undergraduate medical training curriculum.